Hysteresis modeling of reinforced concrete structures : state of the art - Sengupta, Piyali (2018)
Hysteresis modeling of reinforced concrete (RC) structures requires a constitutive relationship capable of producing requisite strength and stiffness degradation and pinching at all displacement levels. Moreover, the hysteresis model must be generic, computationally efficient, and mathematically tractable so as to perform satisfactorily with random input functions. Thus, development of hysteresis models with the entire prerequisites may become stringent considering the numerous parameters contributing to the structural behavior. Hence, an extensive literature review is conducted to comprehend the hysteresis models of RC structures developed by various researchers. Then, a comprehensive synopsis of the state of the art along with the substantive findings is reported in the present paper. Thereafter, a comparative study between the existing hysteresis models and the experimental results of RC structural components under quasi-static cyclic loading is conducted to evaluate the performance of the hysteresis models.